Rational Site-Directed Mutations of the LLP-1 and LLP-2 Lentivirus Lytic Peptide Domains in the Intracytoplasmic Tail of Human Immunodeficiency Virus Type 1 gp41 Indicate Common Functions in Cell-Cell Fusion but Distinct Roles in Virion Envelope Incorporation - Kalia, Vandana (American Society for Microbiology, 2003)
Two highly conserved cationic amphipathic α-helical motifs, designated lentivirus lytic peptides 1 and 2 (LLP-1 and LLP-2), have been characterized in the carboxyl terminus of the transmembrane (TM) envelope glycoprotein (Env) of lentiviruses . Although various properties have been attributed to these domains, their structural and functional significance is not clearly understood. To determine the specific contributions of the Env LLP domains to Env expression, processing, and incorporation and to viral replication and syncytium induction, site-directed LLP mutants of a primary dualtropic infectious human immunodeficiency virus type 1 (HIV-1) isolate (ME46) were examined. Substitutions were made for highly conserved arginine residues in either the LLP-1 or LLP-2 domain (MX1 or MX2, respectively) or in both domains (MX4). The HIV-1 mutants with altered LLP domains demonstrated distinct phenotypes. The LLP-1 mutants (MX1 and MX4) were replication defective and showed an average of 85% decrease in infectivity, which was associated with an evident decrease in gp41 incorporation into virions without a significant decrease in Env expression or processing in transfected 293T cells. In contrast, MX2 virus was replication competent and incorporated a full complement of Env into its virions, indicating a differential role for the LLP-1 domain in Env incorporation. Interestingly, the replication-competent MX2 virus was impaired in its ability to induce syncytia in T-cell lines. This defect in cell-cell fusion did not correlate with apparent defects in the levels of cell surface Env expression, oligomerization, or conformation. The lack of syncytium formation, however, correlated with a decrease of about 90% in MX2 Env fusogenicity compared to that of wild-type Env in quantitative luciferase-based cell-cell fusion assays. The LLP-1 mutant MX1 and MX4 Envs also exhibited an average of 80% decrease in fusogenicity. Altogether, these results demonstrate for the first time that the highly conserved LLP domains perform critical but distinct functions in Env incorporation and fusogenicity.